Opportunities For Integrating Environmental Education With Digital Technologies - Kamolov Bakhtiyor Xasanboyevich (European International Journal of Pedagogics, 2026)
This article examines the opportunities for integrating environmental education with digital technologies from a scientific and methodological perspective. It explores the effectiveness of interactive platforms, artificial intelligence-based learning systems, and digital simulations in shaping ecological awareness. Moreover, the study investigates how the integration of pedagogical methods and technological approaches can strategically foster sustainable development concepts, environmental responsibility, and socio-practical competencies among students and learners. The findings provide a scientific basis for modernizing environmental education, designing innovative learning processes, and utilizing digital resources to cultivate ecological culture and consciousness in contemporary educational contexts.